Burnout Among Business Students and Its Impact On Academic Performance - Habib Ahmed; Syed Moin ud Din Shah (iRASD Journal of Management)
Purpose: Purpose of this research is to check the impact of Burnout among with Work Load and Stress on the Academic Performance of the university and thus then the ways to cope up with the burnout and then to get maximum academic performance.